The Enigmatic Function Orb - Muhammad Faiz Anuar; Muhammad Riefdy Masrul Hisham; Muhammad Haziq Iskandar Shah; Nurhidaya Mohamad Jan; Siti Munirah Mohd (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan